Pelatihan Pembuatan Pakan Fermentasi Dalam Penyediaan Pakan Fermentasi Di Kelompok Tani-Ternak Di Kabupaten Majene - Dewi Puspitasari; Evi Restiana; Lahming; Baso Riadi Husda; Muhammad Bhilal Halim (Vokatek: Jurnal Pengabdian Masyarakat, 2023)
Agricultural waste that is not processed properly will cause environmental pollution. in Banggae District, Majene Regency have agricultural waste that has not been utilized optimally and also farmers who own livestock, so the aim of this service is to provide education and training regarding fermented feed for livestock. This activity is carried outtake place in June 2023 in Banggae District, Majene Regency, West Sulawesi. Participants who took part in this activity were: member Livestock group in Banggae' District. The method used is socialization, training theory and practice, as well as assistance in making fermented feed. Results of activities shows that fermented feed is very useful for dealing with animal feed, especially in dry season. The training activities went well and were useful for realizing feed independence by utilizing local potential agricultural waste. Mentoring activities are still needed for program sustainability. Fermented feed has better nutritional value and preferably livestock so that it can increase livestock production.